Persepsi pelajar terhadap penggunaan video dan Padlet (PVdP) dalam pengajaran dan pembelajaran subjek pemikiran dan tamadun Islam / Wan Noor Hazlina Wan Jusoh ... [et al.] - Wan Jusoh, Wan Noor Hazlina; Abd Ghani, Ruhaizah; Mohd Noor, Nor Adila; Awang, Azarudin; Sulaiman, Noor Hasyimah (2019)
Islamic Thought and Civilization (CTU151) is a compulsory course for second year diploma Muslim students in Universiti Teknologi MARA (UiTM). Conventional methods of teaching and learning (T&L) are quite dull and failed to tackle students' interest in the subject. Therefore, the usage of video and Padlet is proposed to be an alternative for teaching method in settling the problem faced during the T&L process. This research aims at measuring students' perception on the suitability of the proposed methods of T&L either inside or outside the classroom. Pilot study was conducted using questionnaire by distributing it to 35 respondents and the data were analyzed using SPSS version 22. Then, descriptive analysis was used to measure students' perception on the related questions. The result shows that high scale of the students' perception on the using of PVdP at average mean score of 3.93. The finding implies that using the PVdP innovative method in the classroom managed to overcome the classroom dullness environment, led the students to become happier, and improvised their understanding because Padlet is a Web 2.0 application that could be used for learning collaboration and as a communication tool among students. In fact, technology integration through video and Padlet is one of the mechanisms that stimulates good T&L process and also helps to boost students' performance in this course.